Clinical-Pathological, Immunohistochemical, and Genetic Characterization of a Series of Posterior Pituitary Tumors. Issue 1 (19th November 2020) - Barresi, Valeria; Simbolo, Michele; Gessi, Marco; Rossi, Sabrina; Caffo, Maria; Eccher, Albino; Angileri, Filippo Flavio; Cannavò, Salvatore; Brunelli, Matteo; Scarpa, Aldo
Abstract: Posterior pituitary tumors are supposed to represent the morphological spectrum of a single entity. Herein, we report the clinical-pathological, immunohistochemical, and genetic features of 5 spindle cell oncocytomas (SCOs), 3 pituicytomas, and 1 granular cell tumor (GCT). SCOs had the highest local invasiveness and affected older subjects. The 3 histotypes differed in the content of spindle cells (predominant in pituicytoma and absent in GCT), presence of lymphocytic infiltrate (in SCO and GCT, but not in the pituicytoma) and EMA/GFAP staining (negative in GCT; EMA-positive/GFAP-negative in 4/5 SCO and GFAP-positive in 3/3 pituicytomas). Three SCOs and 1 pituicytoma analyzed with next-generation sequencing had no mutations in 409 genes. However, 1 SCO had previously unreported homozygous deletion of CDKN2A/B and another of SMARCA4, SMARCB1, and NF2 . All 3 SCOs had loss of heterozygosity of chromosome 1p, while the pituicytoma had chromosome 19 homozygous loss and chromosomes 10, 13q, and 18q loss of heterozygosity. Since 1p and 13q losses were previously reported in 1 pituicytoma and 1 SCO, respectively, our data demonstrate that posterior pituitary tumors share common genetic alterations. The possibility that posterior pituitary tumors are SMARCA4/SMARCB1 -deficient should be kept in mind in the differential diagnosis toward other entities.